Zika virus disease knowledge among the future health-care providers of the United Arab Emirates - Syed Arman Rabbani; Farhan Mustafa; Tasneem Shouqair; Itaf Mohamad; Nada Tahsin (Wolters Kluwer Medknow Publications, 2018)
Zika virus (ZIKV) disease has become a major public health concern. Although there are no reported cases of ZIKV disease in the United Arab Emirates (UAE), there is a potential risk of transmission due to large expatriate population and high influx of international travelers. This cross-sectional study was conducted to assess the knowledge of ZIKV disease among the students of a medical and health sciences university in the UAE. Their knowledge of ZIKV disease was assessed using a specially designed, pretested, and validated questionnaire. Of the 500 respondents included in the final analysis, 314 (62.8%) respondents presented with poor knowledge of ZIKV disease. The mean knowledge score of the study population was 10.48 ± 2.48 out of a maximum of 17. Gender, college and year of study, nationality and attendance in lecture/conference/workshop on Zika were significantly associated with the level of knowledge. The males possessed significantly (P = 0.046) better knowledge as compared to the females. Students of medical college had significantly (P = 0.005) better knowledge as compared to students of other colleges. The level of knowledge improved significantly (P = 0.026) as the year of study progressed. There is a need for medical and paramedical students to update their knowledge of ZIKV disease as they are the future health-care providers who will be responsible for creating awareness about such outbreaks and their preventive measures.